Silver-mediated direct trifluoromethoxylation of α-diazo esters via the −OCF3 anion. Issue 47 (28th April 2016) - Zha, Gao-Feng; Han, Jia-Bin; Hu, Xiao-Qian; Qin, Hua-Li; Fang, Wan-Yin; Zhang, Cheng-Pan
Abstract : Silver-mediated direct trifluoromethoxylation of α-diazo esters and ketosteroid was disclosed. Abstract : Silver-mediated direct trifluoromethoxylation of α-diazo esters and ketosteroid was disclosed. The reactions of alkyl α-diazo arylacetates with AgOCF3 or CF3 SO2 OCF3 /AgF at −30 to 10 °C under a N2 atmosphere provided α-trifluoromethoxyl arylacetates in up to 90% yield, while alkyl α-diazo vinylacetates reacting with CF3 SO2 OCF3 /AgF or AgOCF3 afforded γ-trifluoromethoxyl α, β-unsaturated esters in up to 94% yield. The α-diazo ketosteroid was also trifluoromethoxylated under the standard reaction conditions. This protocol allows for an effective and convenient access to a large number of synthetic building blocks, which are promising in the development of new functional OCF3 -molecules.